Pengaruh Citra Merek, Harga, Kualitas Produk Terhadap Keputusan Pembelian Kendaraan Hybrid Toyota Kijang Innova Zenix: (Studi Kasus Pada Masyarakat di Bandar Lampung) - Eldiansyah, Resky; Suwarni, Emi (JURNAL ADMINISTRASI BISNIS (JAB), 2023)
The purpose of this study was to determine 1) whether Brand Image can influence customers in purchasing decisions. 2) whether Price can influence customers in purchasing decisions 3) whether Product Quality can influence customers in purchasing decisions. The population of this study was all customers who knew and bought Toyota Kijang Innova Zenix hybrid vehicles in Bandar Lampung. The sample used in this study had 154 respondents. The sampling method used is a non-probability sample with a purposive sampling technique. Overall, the results of this study are 1) Brand image has a positive effect on Purchasing Decisions, 2) Price has a positive effect on Purchasing Decisions, and 3) Product quality has a positive effect on Purchasing Decisions.